Engagement during a Mixed In-Person and Remotely Delivered Psychological Intervention for Youth with Functional Abdominal Pain Disorders and Anxiety - Alaina K. Miller; Samantha L. Ely; Brittany N. Barber Garcia; Patricia Richardson; Natoshia R. Cunningham (MDPI AG, 2021)
Functional abdominal pain disorders (FAPD) are common disabling pain conditions frequently associated with co-occurring mental health problems such as anxiety. Psychological therapies such as cognitive behavioral therapy (CBT) have been shown to be effective. Therefore, it is important to understand participant engagement (i.e., use of intervention tools) to such approaches, and if engagement impacts treatment response. The Aim to Decrease Anxiety and Pain Treatment (ADAPT) is an effective psychological treatment approach using a blend of in-person sessions and interventionist phone support with self-paced web modules to manage pain and anxiety. The current study used a mixed-methods approach to investigate micro-level and macro-level participant engagement during the ADAPT program. In-person/phone session attendance was high (>95%) although scheduling adjustments were common (25.5%). Varied levels of engagement with web tools were observed. Thematic analysis also revealed variability in patterns of use. Additionally, while participants indicated they generally understood how to use certain skills (e.g., problem solving, detective thinking), and these skills were effective in managing symptoms during treatment, these activities were generally underutilized. Further, participant engagement did not predict response to the ADAPT intervention. These findings are important as the demand for accessible psychotherapeutic tools to manage pain and anxiety is likely to remain high.